Morphological and biochemical resistance to Helicoverpa armigera (Lepidoptera: Noctuidae) in tomato. (December 2022) - Bisht, Kalpana; Yadav, Sunil Kumar; Bhowmik, Sagarika; Singh, N.N.
Abstract: Tomato ( Solanum lycopersicum L.) production in the tropics suffers from depredation by the tomato fruit borer, Helicoverpa armigera (Hübner), causing severe economic losses. Development of H. armigera resistant tomato cultivars in India is very limited due to lack of good sources of resistance for breeding. Use of insect resistant cultivars could reduce indiscriminate use of insecticides. A total of twenty-two tomato genotypes were assessed under field conditions for resistance to H. armigera during 2017–18 and 2018–19. Morphological and biochemical factors associated with the expression of resistance to this pest in tomato were estimated and considered as potential markers of resistance. The six genotypes, Kashi Sharad, Pb Barkha-1, DVRT-1, Pb Barkha-2, DVRT-2 and Pusa Rohit, were least infested by H. armigera with fruit weight loss ranging from 4.63 to 8.71 percent and were classified as resistant. Expression of resistance was associated with higher trichome density on leaves and calyxes, higher fruit pericarp thickness, higher phenol content in leaves and fruits, and lower soluble sugar and protein contents in leaves and fruits. Resistant genotypes of tomato with these factors may be used as sources of resistance in future breeding programs to enhance resistance to H. armigera in commercially cultivated tomato varieties. Graphical abstract: Image 1 Highlights: Tomato production in the tropics suffers from depredation by Helicoverpa armigera. Twenty-two genotypes were assessed for resistance to H. armigera. The genotypes Kashi Sharad, Pb Barkha-1, DVRT-1, Pb Barkha-2, DVRT-2 and Pusa Rohit were classified as resistant. Expression of resistance was associated with trichome density, fruit pericarp thickness and phenol content.